Pemberdayaan Remaja melalui Pelatihan Pembuatan Hand Sanitizer Berbasis Buah Jeruk Nipis dan Belimbing Wuluh di SMK Bina Nusa Tegal - Rosaria Ika Pratiwi; Aldi Budi Riyanta; Heru Nurcahyo (Universitas Muhammadiyah Semarang, 2025)
Hand sanitizer is an innovative instant hand-cleaning product that can be used without rinsing with water. The high alcohol content and other chemicals in hand sanitizer products can cause skin irritation, so it is necessary to innovate in making natural antiseptics using natural ingredients that function as antibacterials. The types of plants that can be applied to make hand sanitizer are lime and star fruit. This community service activity aims to increase knowledge about the benefits of lime and star fruit that grow in the surrounding environment as antibacterials, improve healthy and clean lifestyles to prevent the transmission of bacteria and viruses, and improve skills in making hand sanitizers. The target audience for this community service activity is students of SMK Bina Nusa, Slawi ,lass X, because they are new students so it is relatively easier to develop healthy and clean lifestyle habits. The methods used in this community service activity include socialization or counseling about the benefits of lime and star fruit, as well as a healthy and clean lifestyle to prevent the transmission of bacteria and viruses and training in making hand sanitizers. Community service activities are going well, the students of SMK Bina Nusa Slawi have understood and understand the benefits of lime and star fruit that grow in the surrounding environment as antibacterials, are aware of a healthy and clean lifestyle to prevent the transmission of bacteria and viruses, and have skills in making hand sanitizer as a health product.